DEVELOPMENT OF TECHNOLOGY FOR IODINE MEAT PRODUCTS - Elena Y. Maslova; Nadegda P. Salatkova; Marina V. Kaledina; Natalia D. Lupandina (Вестник Северо-Кавказского федерального университета, 2022)
The data of studies on the use of seaweed in the production of meat products in the shell functionality. The optimal processing methods for the enrichment of the meat product with an organic iodine. Recipe developed production of meat products containing iodine .